Comparison based on kbmi 1 on national private bank risks with conventional and sharia principles - Juniar, Asrid; Pradana, Rilian Gusma Wira; Rahmawati, Rini; Sofyaun, Ashari (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2023)
The purpose of this study is to determine whether there are differences in credit risk, liquidity risk, and market risk in conventional national private banks and Islamic national private banks based on KBMI 1. This study used 24 banks as a sample consisting of 21 conventional banks and 3 Islamic banks from 68 national private banks registered with the OJK which became the population through the purposive sampling method. Data using secondary data obtained from the company's annual statements published on the OJK website and on the company's official website. The data collection of this study used documentation techniques and the method used, and the method used is different test. The results in the tests that have been carried out show that there is no difference in the credit risk of conventional national private banks and Islamic national private banks based on KBMI; There is no difference in the liquidity risk of conventional national private banks and Islamic national private banks based on KBMI; There are no differences in the market risks of conventional national private banks and Islamic national private banks based on KBMI